Increasing Learning Outcomes and Learning Engagement by Using Discovery Learning Assisted by Trello - Ni’mah, Muflihatun; Agustina, Yuli (Transpublika Publisher, 2024)
The increasingly massive digitalization creates new challenges for the world of education in order to produce students who are ready to collaborate, communicate, and discuss at any time and under any conditions. The aim of this research is to implement the Discovery Learning model assisted by Trello to improve the learning outcomes and learning engagement of phase E students in Class X MPLB SMK Nasional Malang. This type of research is classroom action research carried out in 2 cycles with data analysis using percentage comparisons in cycle 1 and cycle 2. The results show that the implementation of this combination is able to maximize learning activities and increase students' learning outcomes. Scores at the end of the cycle increase in both the affective, cognitive and psychomotor domains. students help each other, which has an impact on increasing the speed of completing assignments. Students' learning engagement also increases at the end of the cycle, which can be seen from students becoming more active and participative in working on group projects.